Film capacitors, films and metallized films

By using dielectric films with protrusions or bumps of specific specifications in film capacitors, the problems of insufficient sliding and voltage withstand are solved, and excellent self-healing function and decomposition of gas emission effect are achieved.

CN116325041BActive Publication Date: 2025-01-07MURATA MFG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180067965.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-09
Filing Date
2021-10-06
Publication Date
2025-01-07
Estimated Expiration
2041-10-06

AI Technical Summary

Technical Problem

Existing film capacitors have shortcomings in balancing slip and voltage withstand, and their self-healing function is difficult to effectively perform, especially when the decomposition gas is difficult to dissipate during insulation breakdown.

Method used

A dielectric film containing a first organic material with hydroxyl groups and a second organic material with aromatic isocyanate groups is cured. By forming multiple protrusions or bumps of specific sizes on the film surface, the sliding properties and voltage resistance are improved, and the self-healing function is enhanced.

Benefits of technology

Excellent sliding properties, voltage withstand capability, and self-healing properties of film capacitors are achieved, ensuring that decomposition gases can be effectively released during insulation breakdown, thus improving suppression and self-healing functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116325041B_ABST
    Figure CN116325041B_ABST
Patent Text Reader

Abstract

The film capacitor (10) comprises a wound body (40) formed by winding a dielectric film (110) and a metal layer (220), wherein the dielectric film (110) comprises a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and has a first main surface (110a) and a second main surface (110b) facing each other in the thickness direction, and the metal layer (220) is provided on at least the first main surface (110a) of the dielectric film (110). 10a), there are a plurality of protrusions (120) having a second organic material on the first main surface (110a) of the dielectric film (110), within an area of ​​100 μm×140 μm of the first main surface (110a) of the dielectric film (110), the average diameter of the plurality of protrusions (120) is greater than 0.58 μm and less than 5.98 μm, the average height is greater than 0.11 μm and less than 2.54 μm, and the number of the protrusions is greater than 50 and less than 450.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film capacitor, a film, and a metallized film. Background Art

[0002] As one type of capacitor, a thin film capacitor having the following structure is known, that is, a first metal layer and a second metal layer are arranged opposite to each other with the film sandwiched therebetween while using a flexible film as a dielectric film. Such a thin film capacitor is manufactured, for example, by winding or stacking a thin film forming the first metal layer and a thin film forming the second metal layer.

[0003] When a film capacitor is manufactured by winding a film to make a wound body, the wound body is sometimes pressed to reduce the height of the film capacitor. At this time, if the film has good sliding properties, the wound body can be easily pressed evenly, thereby reducing the height of the film capacitor.

[0004] On the other hand, if a gap is formed between the overlapping films in the wound body, the decomposition gas from the film becomes easy to fly from the inside of the film capacitor when the insulation breaks down, resulting in the recovery of the insulation state of the film, that is, the so-called self-healing function. When the wound body is made, if the film has good sliding properties, it becomes easy to form a gap evenly between the overlapping films, so the self-healing function becomes easy to work.

[0005] As described above, in order to improve the compressibility and self-healing properties of film capacitors, slip properties are sometimes imparted to the film. As a method of imparting slip properties to the film, a method of blending an organic filler in a base resin is disclosed in Patent Document 1. In this way, in the past, slip properties were imparted to the film by blending fillers in the resin to make the surface of the film rough.

[0006] Prior Art Literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-251493 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] However, in the conventional film in which a filler is mixed with a resin, since the dielectric constants of the resin and the filler are different, the electric field tends to be concentrated near the filler, and as a result, the insulation breakdown voltage decreases. Therefore, it can be said that in the conventional film, there is room for improvement in terms of making both sliding property and voltage resistance take into account.

[0011] On the other hand, by making the surface of the film rough, when the film capacitor is manufactured by winding the film, gaps are easily formed between the overlapping films. Therefore, it is believed that the self-healing function becomes easier to work when the insulation is broken.

[0012] However, if the hardness of the rough surface of the film is low, the rough surface of the film becomes easily crushed when the film is wound to manufacture a film capacitor, so it becomes difficult to form a gap between the overlapping films. As a result, when the insulation is broken down, the decomposition gas from the film becomes difficult to disperse from the inside of the film capacitor, so the self-healing function becomes difficult to work.

[0013] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a film capacitor having a dielectric film that has excellent sliding properties and voltage resistance and can impart excellent compressibility and self-healing properties. In addition, the present invention aims to provide a film that can be used as a dielectric film of the above-mentioned film capacitor. Furthermore, the present invention aims to provide a metallized film that can be used in the above-mentioned film capacitor.

[0014] Technical solutions to solve problems

[0015] In the first aspect, the film capacitor of the present invention is characterized in that it includes a wound body formed by winding a dielectric film and a metal layer, the dielectric film containing a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and having a first main surface and a second main surface facing each other in the thickness direction, the metal layer is provided on at least the first main surface of the dielectric film, a plurality of protrusions having the second organic material are present on the first main surface of the dielectric film, and within an area of ​​100 μm×140 μm on the first main surface of the dielectric film, the plurality of protrusions have an average diameter of 0.58 μm or more and 5.98 μm or less, an average height of 0.11 μm or more and 2.54 μm or less, and a number of the protrusions is 50 or more and 450 or less.

[0016] In a second aspect, a film capacitor of the present invention is characterized in that it includes a wound body formed by winding a dielectric film and a metal layer, the dielectric film including a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and having a first main surface and a second main surface facing each other in a thickness direction, the metal layer being provided on at least the first main surface of the dielectric film, a plurality of protrusions having the second organic material being present on the first main surface of the dielectric film, a plurality of convex portions along the plurality of protrusions being present on a surface of the metal layer provided on the first main surface of the dielectric film on the side opposite to the first main surface of the dielectric film, and within an area of ​​100 μm×140 μm on the surface of the metal layer, the plurality of convex portions have an average diameter of 0.60 μm or more and 6.13 μm or less, an average height of 0.13 μm or more and 2.63 μm or less, and a number of the plurality of protrusions being 50 or more and 450 or less.

[0017] The film of the present invention is characterized in that it comprises a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and has a first main surface and a second main surface opposing each other in the thickness direction, a plurality of protrusions having the second organic material are present on the first main surface, and within an area of ​​100 μm×140 μm of the first main surface, the plurality of protrusions have an average diameter of not less than 0.58 μm and not more than 5.98 μm, an average height of not less than 0.11 μm and not more than 2.54 μm, and a number of the protrusions is not less than 50 and not more than 450.

[0018] The metallized film of the present invention is characterized in that it comprises: a film comprising a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and having a first main surface and a second main surface opposite to each other in the thickness direction; and a metal layer provided on at least the first main surface of the film, wherein a plurality of protrusions having the second organic material are present on the first main surface of the film, and a plurality of convex portions along the plurality of protrusions are present on the surface of the metal layer provided on the first main surface of the film on the opposite side to the first main surface of the film, wherein within an area of ​​100 μm×140 μm on the surface of the metal layer, the plurality of convex portions have an average diameter of not less than 0.60 μm and not more than 6.13 μm, an average height of not less than 0.13 μm and not more than 2.63 μm, and a number of the plurality of convex portions is not less than 50 and not more than 450.

[0019] Effects of the Invention

[0020] According to the present invention, a film capacitor having a dielectric film having excellent sliding properties and voltage resistance and being able to impart excellent compressibility and self-healing properties can be provided. In addition, according to the present invention, a film that can be used as a dielectric film of the above-mentioned film capacitor can be provided. Furthermore, according to the present invention, a metallized film that can be used in the above-mentioned film capacitor can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 FIG. 1 is a schematic perspective view showing an example of the film capacitor of the present invention.

[0022] Figure 2 is shown with Figure 1 A schematic cross-sectional view of the portion corresponding to the line segment A1 - A2 in FIG.

[0023] Figure 3 It is shown Figure 1 as well as Figure 2 A three-dimensional schematic diagram of an example of a wound body in.

[0024] Figure 4 FIG. 1 is a schematic plan view showing an example of a metal layer in which a fuse portion is provided.

[0025] Figure 5 This is a schematic plan view showing an example of the film of the present invention.

[0026] Figure 6 is shown with Figure 5 A schematic cross-sectional view of the portion corresponding to the line segment B1 - B2 in FIG.

[0027] Figure 7 FIG. 1 is a schematic plan view showing an example of a metallized film constituting the film capacitor of the present invention.

[0028] Figure 8 is shown with Figure 7 A schematic cross-sectional view of the portion corresponding to the line segment C1-C2 in FIG. DETAILED DESCRIPTION

[0029] The following describes the film capacitor of the present invention, the film of the present invention, and the metallized film of the present invention. In addition, the present invention is not limited to the following structure, and can be appropriately changed within the scope of the present invention. In addition, the product of combining multiple preferred structures described below is also the present invention.

[0030] In the first and second modes, the film capacitor of the present invention comprises a wound body formed by winding a dielectric film and a metal layer, wherein the dielectric film comprises a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and has a first main surface and a second main surface opposite to each other in the thickness direction, and the metal layer is arranged on at least the first main surface of the dielectric film.

[0031] When the first aspect and the second aspect of the film capacitor of the present invention are not particularly distinguished, they are simply referred to as "film capacitor of the present invention".

[0032] Hereinafter, as an example of the film capacitor of the present invention, a so-called wound film capacitor in which a metalized film having a metal layer provided on at least one main surface of a dielectric film is wound in a stacked state will be described.

[0033] Figure 1 FIG. 1 is a schematic perspective view showing an example of the film capacitor of the present invention. Figure 2 is shown with Figure 1 A schematic cross-sectional view of the portion corresponding to the line segment A1 - A2 in FIG. Figure 3 It is shown Figure 1 as well as Figure 2 A three-dimensional schematic diagram of an example of a wound body in.

[0034] In this manual, if Figure 1 , Figure 2 ,as well as Figure 3 As shown, the stacking direction and the width direction in the film capacitor are respectively set to directions determined by T and W. In addition, in the wound film capacitor, it can also be said that there are multiple stacking directions, but in this specification, it is set to be a direction determined by T. Here, the stacking direction T and the width direction W are orthogonal to each other.

[0035] like Figure 1 as well as Figure 2 As shown, the film capacitor 10 includes a winding body 40, a first external electrode 41 provided on one end surface of the winding body 40, and a second external electrode 42 provided on the other end surface of the winding body 40. Here, both end surfaces of the winding body 40 face each other in the width direction W.

[0036] like Figure 2 as well as Figure 3 As shown, wound body 40 is a wound body in which first metallized film 11 and second metallized film 12 are wound in a stacked state in stacking direction T. That is, film capacitor 10 is a wound-type film capacitor having wound body 40 .

[0037] In the film capacitor 10, from the viewpoint of reducing the height of the film capacitor 10, it is preferred that the cross-sectional shape of the wound body 40 is a flat shape when observing the cross-section perpendicular to the winding axis direction of the wound body 40. More specifically, it is preferred that the wound body 40 is pressed into a flat shape such as an ellipse or an elongated circle, and that the thickness is smaller than when the cross-sectional shape of the wound body 40 is a perfect circle.

[0038] Whether the wound body is pressed so that the cross-sectional shape thereof is flat can be confirmed by, for example, whether there is a pressing mark on the wound body.

[0039] Film capacitor 10 may have a cylindrical winding axis. The winding axis is disposed on the central axis of first metallized film 11 and second metallized film 12 in a wound state and serves as a winding axis when first metallized film 11 and second metallized film 12 are wound.

[0040] The first metalized film 11 includes a first dielectric film 13 and a first metal layer 15 .

[0041] The first dielectric film 13 has a thickness direction ( Figure 2 1 and 13 b are the first main surface 13 a and the second main surface 13 b facing each other in the stacking direction T).

[0042] The first metal layer 15 is provided on the first main surface 13a of the first dielectric film 13. More specifically, the first metal layer 15 is provided to reach one side edge of the first dielectric film 13 in the width direction W but not to reach the other side edge of the first dielectric film 13.

[0043] The second metalized film 12 includes a second dielectric film 14 and a second metal layer 16 .

[0044] The second dielectric film 14 has a thickness direction ( Figure 2 1 and 2 are the first main surface 14a and the second main surface 14b facing each other in the stacking direction T).

[0045] The second metal layer 16 is provided on the first main surface 14a of the second dielectric film 14. More specifically, the second metal layer 16 is provided so as not to reach one side edge of the second dielectric film 14 in the width direction W but to reach the other side edge of the second dielectric film 14.

[0046] In the wound body 40, the adjacent first metallized films 11 and second metallized films 12 are offset in the width direction W so that the end of the first metal layer 15 on the side reaching the side edge of the first dielectric film 13 is exposed at one end surface of the wound body 40, and the end of the second metal layer 16 on the side reaching the side edge of the second dielectric film 14 is exposed at the other end surface of the wound body 40.

[0047] Since the wound body 40 is formed by winding the first metallized film 11 and the second metallized film 12 in a state of being stacked in the stacking direction T, it can also be said that it is a wound body formed by winding the first metal layer 15, the first dielectric film 13, the second metal layer 16, and the second dielectric film 14 in a state of being stacked in sequence in the stacking direction T.

[0048] In the wound body 40, the first metallized film 11 and the second metallized film 12 are wound in a stacked state in the stacking direction T, so that the first metallized film 11 is located inside the second metallized film 12, the first metal layer 15 is located inside the first dielectric film 13, and the second metal layer 16 is located inside the second dielectric film 14. That is, the first metal layer 15 and the second metal layer 16 are located opposite to each other with the first dielectric film 13 or the second dielectric film 14 interposed therebetween.

[0049] The second metal layer 16 may be provided on the second main surface 13b of the first dielectric film 13 instead of the first main surface 14a of the second dielectric film 14. In this case, in the wound body 40, the metallized film in which the first metal layer 15 is provided on the first main surface 13a of the first dielectric film 13 and the second metal layer 16 is provided on the second main surface 13b, and the second dielectric film 14 are wound in a stacked state in the stacking direction T.

[0050] It is preferable that a fuse portion is provided in each of the first metal layer 15 and the second metal layer 16 .

[0051] Figure 4 FIG. 1 is a schematic plan view showing an example of a metal layer in which a fuse portion is provided.

[0052] like Figure 4 As shown, the first metal layer 15 is provided with a plurality of divided electrode portions 61 , an electrode portion 62 , and a fuse portion 63 .

[0053] The plurality of divided electrode portions 61 are divided by insulating slits 64 and are portions that face the second metal layer 16 in the wound body 40 .

[0054] The electrode portion 62 is adjacent to the plurality of divided electrode portions 61 with the insulating slit 64 interposed therebetween, and is a portion that does not face the second metal layer 16 in the wound body 40 .

[0055] The fuse portion 63 is a portion that connects the divided electrode portions 61 and the electrode portions 62 , and is thinner than the divided electrode portions 61 and the electrode portions 62 .

[0056] The electrode pattern of the first metal layer 15 in which the fuse portion is provided is Figure 4In addition to the electrode pattern shown, for example, the electrode pattern disclosed in Japanese Patent Application Laid-Open No. 2004-363431, Japanese Patent Application Laid-Open No. 5-251266, etc. The same applies to the electrode pattern of the second metal layer 16 provided with the fuse portion.

[0057] The first external electrode 41 is provided on one end surface of the wound body 40 , and is connected to the first metal layer 15 by being in contact with the exposed end portion of the first metal layer 15 .

[0058] From the viewpoint of connectivity between first metal layer 15 and first external electrode 41 , it is preferred that first metalized film 11 protrude in width direction W relative to second metalized film 12 at one end surface of wound body 40 .

[0059] The second external electrode 42 is provided on the other end surface of the wound body 40 , and is connected to the second metal layer 16 by being in contact with the exposed end portion of the second metal layer 16 .

[0060] From the viewpoint of connectivity between the second metal layer 16 and the second external electrode 42 , it is preferred that the second metalized film 12 protrudes in the width direction W relative to the first metalized film 11 at the other end surface of the wound body 40 .

[0061] Examples of the constituent materials of the first external electrode 41 and the second external electrode 42 include metals such as zinc, aluminum, tin, and zinc-aluminum alloys.

[0062] The first external electrode 41 and the second external electrode 42 are each preferably formed by thermally spraying the above-mentioned metal on one end surface and the other end surface of the wound body 40 .

[0063] The structure of the winding body 40 can also be Figure 2 For example, the first metal layer 15 in the first metalized film 11 may be divided into two metal layers in the width direction W, one metal layer reaching one side edge of the first dielectric film 13, and the other metal layer reaching the other side edge of the first dielectric film 13. In this case, if one metal layer in the first metal layer 15 is connected to the first external electrode 41 and the other metal layer is connected to the second external electrode 42, and at the same time, the second metal layer 16 is not connected to both the first external electrode 41 and the second external electrode 42, a capacitor can be formed between the first metal layer 15 and the second metal layer 16.

[0064] In the film capacitor of the present invention, the film of the present invention can be used as the dielectric film.

[0065] The film of the present invention includes a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and has a first main surface and a second main surface facing each other in the thickness direction.

[0066] Figure 5 This is a schematic plan view showing an example of the film of the present invention. Figure 6 is shown with Figure 5 A schematic cross-sectional view of the portion corresponding to the line segment B1 - B2 in FIG.

[0067] like Figure 5 as well as Figure 6 As shown, the film (dielectric film) 110 has a first main surface 110 a and a second main surface 110 b which are opposed to each other in the thickness direction.

[0068] The film 110 includes a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds. More specifically, the film 110 includes a cured product having a urethane bond obtained by reacting a hydroxyl group (OH group) of the first organic material and an isocyanate group (NCO group) of the second organic material.

[0069] The presence of urethane bonds in the film can be confirmed by analysis using a Fourier transform infrared spectrophotometer (FT-IR).

[0070] The first organic material is preferably a polyol having a plurality of hydroxyl groups in the molecule.

[0071] Examples of the polyol include polyvinyl acetals such as polyvinyl acetal, polyether polyols such as phenoxy resins, and polyester polyols.

[0072] As the polyol, a phenoxy resin is preferred.

[0073] As the first organic material, a plurality of materials may be used in combination.

[0074] The second organic material can also be said to be a so-called aromatic isocyanate having an isocyanate group among aromatic compounds.

[0075] The second organic material reacts with the hydroxyl group of the first organic material to form a cross-linked structure, thereby functioning as a curing agent for curing the resin solution when the thin film 110 is manufactured.

[0076] The second organic material is preferably an aromatic compound having a plurality of isocyanate groups in the molecule, so-called aromatic polyisocyanate.

[0077] Examples of the aromatic polyisocyanate include diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), etc. As the aromatic polyisocyanate, modified products of these aromatic polyisocyanates may also be used.

[0078] As the aromatic polyisocyanate, MDI is preferred. As MDI, for example, polymeric MDI or monomeric MDI can be used.

[0079] As the second organic material, a plurality of materials may be used in combination.

[0080] Film 110 Figure 2 In the film capacitor 10 shown in the figure, the film 110 may be used for both the first dielectric film 13 and the second dielectric film 14, or may be used for only one of the first dielectric film 13 and the second dielectric film 14. Figure 2 In the case of both the first dielectric film 13 and the second dielectric film 14 of the thin film capacitor 10 shown, the compositions of the first dielectric film 13 and the second dielectric film 14 may be different from each other, but are preferably the same as each other.

[0081] The film 110 is produced by applying a resin solution containing a first organic material and a second organic material to the surface of a substrate, drying the solution, and then curing the solution by heat treatment. The obtained film 110 is used in a state of being peeled off from the substrate.

[0082] In the thin film of the present invention, a plurality of protrusions including the second organic material are present on the first main surface.

[0083] In Figure 5 as well as Figure 6 In the illustrated film 110 , a plurality of protrusions 120 are present on the first main surface 110 a . In addition, a flat portion 130 is present on the first main surface 110 a of the film 110 , and the protrusions 120 are not present in the flat portion 130 .

[0084] The presence of the protrusions can be confirmed as black-looking portions by observing the first main surface of the thin film with a scanning electron microscope (SEM).

[0085] The protrusion 120 includes the second organic material, that is, aromatic isocyanate. More specifically, the aromatic isocyanate included in the protrusion 120 is derived from the aromatic isocyanate constituting the cured product included in the film 110 .

[0086] Since the protrusion 120 has an aromatic isocyanate, the hardness of the protrusion 120 increases due to the aromatic ring of the aromatic isocyanate. Therefore, when the film 110 is used to manufacture a film capacitor, even if the film 110 is wound or pressed after winding, the protrusion 120 is not easily crushed, so it is easy to form a gap between the overlapping films 110. As a result, when the insulation is broken, the decomposition gas from the film 110 becomes easy to fly out from the inside of the film capacitor, so the self-healing property of the film capacitor becomes excellent.

[0087] In contrast, when the protrusion 120 has aliphatic isocyanate, the hardness of the protrusion 120 is lower than when the protrusion 120 has aromatic isocyanate. Therefore, when the film 110 is used to manufacture a film capacitor, if the film 110 is wound or pressed after winding, the protrusion 120 becomes easy to be crushed, so it becomes difficult to form a gap between the overlapping films 110. As a result, when the insulation is broken, the decomposition gas from the film 110 becomes difficult to disperse from the inside of the film capacitor, so the self-healing property of the film capacitor is reduced.

[0088] In addition, even if the protrusion 120 has aromatic isocyanate, for example, if the average height of the protrusion described later is less than 0.11 μm or the number of the protrusion described later is less than 50, it becomes difficult to form a gap between the overlapping films 110 when the film 110 is wound to manufacture a thin film capacitor, and thus the self-healing property of the thin film capacitor is also reduced.

[0089] The presence of aromatic isocyanate in the protrusions can be confirmed as follows. First, a Fourier transform infrared spectrophotometer (FT-IR) "FT / IR-4100ST" manufactured by JASCO Corporation was used to measure the wavelength range of 500 cm -1 Above 4000cm -1 Next, the infrared absorption spectrum of the protrusions is measured by attenuated total reflection (ATR). Then, in the infrared absorption spectrum of the protrusions, by confirming the detection of the absorption peaks of the aromatic ring and the isocyanate group, it can be confirmed that the protrusions have aromatic isocyanate. For example, when MDI is used as the aromatic isocyanate, in the infrared absorption spectrum, at 1450 cm -1 Above and 1550cm -1 The absorption peaks of aromatic rings can be detected in the following wavenumber ranges: 2200 cm -1 Above and 2400cm -1 The absorption peak of the isocyanate group can be detected in the following wave number range.

[0090] Furthermore, by confirming the detection of the absorption peak of the aromatic ring and the absorption peak of the isocyanate group in the infrared absorption spectrum of the flat portion in the same manner, it can be confirmed that the aromatic isocyanate contained in the protrusions is derived from the aromatic isocyanate in the cured product constituting the film.

[0091] In the film of the present invention, within an area of ​​100 μm×140 μm on the first main surface, the plurality of protrusions have an average diameter of 0.58 μm to 5.98 μm, an average height of 0.11 μm to 2.54 μm, and a number of 50 to 450.

[0092] exist Figure 5 as well as Figure 6 In the thin film 110 shown, within the area of ​​100 μm×140 μm on the first main surface 110 a , the average diameter of the plurality of protrusions 120 is 0.58 μm to 5.98 μm, the average height is 0.11 μm to 2.54 μm, and the number is 50 to 450.

[0093] In order to improve the sliding property when the films 110 are slid against each other, it is important to reduce the contact area between the films 110. From this point of view, in the film 110, as described above, there are a plurality of protrusions 120 on the first main surface 110a, and it is intended to reduce the contact area between the films 110 when the films 110 are slid against each other. However, depending on the average diameter, average height, and number of the plurality of protrusions 120, it is sometimes impossible to take both sliding property and voltage resistance into account. In this regard, within the above-mentioned area range of the first main surface 110a of the film 110, the average diameter of the plurality of protrusions 120 is 0.58 μm or more and 5.98 μm or less, the average height is 0.11 μm or more and 2.54 μm or less, and the number is 50 or more and 450 or less, so that the sliding property and voltage resistance of the film 110 become excellent. Furthermore, since the sliding property of the film 110 becomes excellent, when the film 110 is wound to form a film capacitor, the compressibility and self-healing property are improved.

[0094] When the average diameter of the protrusions 120 is less than 0.58 μm, the contact area between the flat portions 130 is likely to increase when the films 110 slide against each other, thereby reducing the slidability. When the average diameter of the protrusions 120 is greater than 5.98 μm, the contact area between the protrusions 120 is likely to increase when the films 110 slide against each other, thereby reducing the slidability.

[0095] When the average height of the protrusions 120 is less than 0.11 μm, the contact area between the flat portions 130 is likely to increase when the films 110 slide against each other, thereby reducing the slidability. When the average height of the protrusions 120 is greater than 2.54 μm, the electric field is likely to concentrate near the protrusions 120, thereby reducing the withstand voltage.

[0096] When the number of protrusions 120 is less than 50, the contact area between the flat portions 130 is likely to increase when the films 110 slide against each other, thereby reducing the slidability. When the number of protrusions 120 is more than 450, the number of locations where the electric field is likely to concentrate, such as the protrusions 120, increases, thereby reducing the withstand voltage.

[0097] Within the above-mentioned area range of the first main surface 110a of the film 110, as long as the average diameter of the plurality of protrusions 120 is greater than 0.58 μm and less than 5.98 μm, the average height is greater than 0.11 μm and less than 2.54 μm, and the number is greater than 50 and less than 450, then in addition to the plurality of protrusions 120, a plurality of recesses may also exist on the first main surface 110a of the film 110.

[0098] The average diameter of the protrusions present on the first main surface of the film can be determined as follows. First, the first main surface of the film is magnified to 100 times using a laser microscope "VK-8700" manufactured by Keyence Corporation, and an area range of 100μm×140μm is observed. At this time, aluminum with a thickness of 10nm can also be pre-deposited on the first main surface of the film. Secondly, within the above-mentioned area range, 30 protrusions with a diameter of 0.02μm or more are selected in a range where the diameter is relatively consistent. Then, for each of the 30 selected protrusions, using the dedicated analysis software "VK-analyzer" of the laser microscope "VK-8700" manufactured by Keyence Corporation, in the 2-point designation mode of the automatic measurement mode, 2 points are selected so that the long diameter (maximum length) of the protrusion of the measurement object is included. Thus, the cross-section corresponding to the straight line between the selected 2 points is displayed. Then, the measurement mode is set to "width", the detection mode is set to "pattern", the detection chart is set to "light differential", and the detection object is set to "outside-outside". Furthermore, the lower threshold value is set to be located above the lower inflection point 2 of the light amount differential value. Furthermore, the upper threshold value is set to be located below the upper inflection point 2 of the light amount differential value. Under such setting conditions, for each of the 30 protrusions, the following is measured: Figure 6 The width R1 of the protrusion 120 shown is determined as the average value of the obtained measured values ​​as the average diameter of the protrusion.

[0099] The average height of the protrusions present on the first main surface of the film can be determined as follows. First, for each of the 30 protrusions selected when determining the average diameter of the protrusions, use the dedicated analysis software "VK-analyzer" of the laser microscope "VK-8700" manufactured by Keyence Corporation, and in the 2-point designation mode of the automatic analysis mode, select 2 points so that the long axis of the protrusion is included and the diameter of the protrusion is greater than 50% and less than 70% of the length of the selected range. As a result, the section corresponding to the straight line between the two selected points is displayed. Then, set the measurement mode to "height", the detection mode to "peak and valley", and the detection chart to "height". Furthermore, the lower threshold value is set to 0.01 μm above the lowest height point of the section. In addition, the upper threshold value is set to 0.01 μm below the highest height point of the section. Under such setting conditions, for each of the 30 protrusions, the following is measured. Figure 6 The height H1 of the protrusion 120 shown is obtained by taking the average of the obtained measured values ​​as the average height of the protrusion.

[0100] The number of protrusions present on the first main surface of the film can be determined by counting the number of protrusions having a diameter of 0.02 μm or more in the same area as that used to determine the average diameter of the protrusions.

[0101] The planar shape of the protrusion 120 may be as follows: Figure 5 The circular shape shown may also be an elliptical shape or other shapes.

[0102] The planar shapes of the protrusions 120 may be the same as or different from each other.

[0103] The cross-sectional shape of the protrusion 120 may be as follows: Figure 6 The tapered shape shown may also be a shape other than a tapered shape.

[0104] The cross-sectional shapes of the protrusions 120 may be the same as or different from each other.

[0105] The top surface of the protrusion 120 is preferably as follows Figure 6 In this case, when the films 110 are slid against each other, the contact area between the protrusions 120 is likely to be reduced, so the sliding property is likely to be improved. In addition, the top surface of the protrusion 120 may not be concave.

[0106] In addition, the protrusion 120 may have a sharp tip or a rounded tip.

[0107] There are no protrusions on the second main surface 110b of the film 110, but there may be a plurality of protrusions. In this case, within the area of ​​100 μm×140 μm of the second main surface 110b of the film 110, the plurality of protrusions existing on the second main surface 110b preferably have an average diameter of 0.58 μm or more and 5.98 μm or less, an average height of 0.11 μm or more and 2.54 μm or less, and a number of 50 or more and 450 or less. In this case, in addition to the plurality of protrusions, there may be a plurality of recesses on the second main surface 110b of the film 110.

[0108] When there are multiple protrusions on the second main surface of the film, the average diameter, average height, and number of these protrusions can be determined in the same way as the average diameter, average height, and number of protrusions present on the first main surface of the film, except that the observation object is set to the second main surface of the film.

[0109] In the film of the present invention, it is preferred that the static friction coefficient on the first main surface side is 1.0 or less.

[0110] exist Figure 5 as well as Figure 6 In the film 110 shown, the static friction coefficient on the first main surface 110a side is preferably 1.0 or less. In this case, the film 110 has extremely excellent sliding properties.

[0111] On the other hand, if the static friction coefficient of the film 110 on the first main surface 110a side becomes too small, the film 110 may be wound in the width direction when the film 110 is wound to manufacture a film capacitor, and it may be difficult to form an external electrode on the end surface of the resulting wound body in the subsequent process. From this point of view, the static friction coefficient of the film 110 on the first main surface 110a side is preferably 0.1 or more.

[0112] The static friction coefficient of the film can be determined as follows. First, as a test sample, two films are prepared. Here, with respect to the two main surfaces of each test sample, during manufacture, the main surface on the substrate side is defined as the demolding surface, and the main surface on the opposite side of the substrate is defined as the dry surface. More specifically, with respect to each test sample, the dry surface is equivalent to the first main surface, and the demolding surface is equivalent to the second main surface. In addition, the length direction of each test sample is preferably the direction in which tensile stress is applied to the film during the manufacturing process of the film capacitor, for example, the same as the winding direction of the film. Secondly, with respect to one of the two test samples, a square-shaped plate is fixed on the demolding surface so that the dry surface is exposed. In addition, with respect to the other test sample, a square-shaped counterweight with a weight of 200g is attached to the dry surface so that the demolding surface is exposed. Then, the demolding surface of another test sample in a state where a counterweight is attached to the dry surface is abutted against the dry surface of a test sample in a state where a plate is fixed to the demolding surface, so that the length directions are parallel to each other. Then, a weight attached to the dry surface of another measurement sample was mounted on a dynamometer manufactured by IMADA and stretched in the longitudinal direction at a speed of 150 mm / min. At this time, the maximum friction force until the weight began to move with the other measurement sample was read, and the static friction coefficient was calculated based on this value.

[0113] In film 110 , the glass transition temperature is preferably 130° C. or higher. In this case, film 110 has excellent heat resistance, and the guaranteed temperature of a film capacitor including film 110 can be increased to, for example, 125° C. or higher.

[0114] The glass transition temperature of the film can be determined as follows. First, using the dynamic viscoelasticity measurement (DMA) device "RSA-III" manufactured by TA Instruments, the film is heated from room temperature to 250°C at a heating rate of 10°C / min, while the storage modulus and loss modulus of the film are measured under the measurement conditions of setting the measurement frequency to 10 rad / sec and the strain to 0.1%. Then, the temperature at which the loss tangent (tanδ) represented by the loss modulus / storage modulus shows the maximum peak is determined as the glass transition temperature.

[0115] The thickness S of the thin film 110 is preferably greater than or equal to 1 μm and less than or equal to 10 μm, and more preferably greater than or equal to 3 μm and less than or equal to 5 μm.

[0116] like Figure 6 As shown, the thickness S of the film is a thickness determined at a position where the protrusion 120 does not exist.

[0117] The thickness of the thin film can be measured using an optical film thickness meter.

[0118] The film of the present invention can be made into a metalized film by providing a metal layer on at least the first main surface, and can constitute the film capacitor of the present invention.

[0119] Figure 7 FIG. 1 is a schematic plan view showing an example of a metallized film constituting the film capacitor of the present invention. Figure 8 is shown with Figure 7 A schematic cross-sectional view of the portion corresponding to the line segment C1-C2 in FIG.

[0120] like Figure 7 as well as Figure 8 As shown, the metallized film 210 has Figure 5 as well as Figure 6 The thin film 110 shown in FIG. 1 and the metal layer 220 provided on the first main surface 110 a of the thin film 110 .

[0121] In the thin film capacitor of the present invention, a plurality of protrusions including the second organic material are present on the first main surface of the dielectric thin film.

[0122] exist Figure 8 In the film 110 shown, Figure 5 as well as Figure 6 The thin film 110 shown in the figure has a plurality of protrusions 120 having aromatic isocyanate as the second organic material on the first main surface 110a. In addition, the thin film 110 has a flat portion 130 on the first main surface 110a where the protrusions 120 are not present.

[0123] Since protrusion 120 contains aromatic isocyanate, a film capacitor including metallized film 210 in which metal layer 220 is provided on first main surface 110 a of film 110 can be made into a film capacitor with excellent self-healing property.

[0124] In the first aspect of the film capacitor of the present invention, within the area of ​​100 μm×140 μm of the first main surface of the dielectric film, the average diameter of the plurality of protrusions is 0.58 μm to 5.98 μm, the average height is 0.11 μm to 2.54 μm, and the number is 50 to 450. Thus, in the first aspect of the film capacitor of the present invention, attention is paid to the plurality of protrusions present on the first main surface of the dielectric film.

[0125] exist Figure 8 In the film 110 shown, Figure 5 as well as Figure 6Similarly, in the illustrated film 110 , within an area of ​​100 μm×140 μm on the first main surface 110 a , the plurality of protrusions 120 have an average diameter of 0.58 μm to 5.98 μm, an average height of 0.11 μm to 2.54 μm, and a number of 50 to 450.

[0126] The film 110 has excellent sliding properties and withstand voltage properties because the average diameter of the plurality of protrusions 120 is 0.58 μm or more and 5.98 μm or less, the average height is 0.11 μm or more and 2.54 μm or less, and the number of the protrusions is 50 or more and 450 or less within the above-mentioned area range of the first main surface 110a of the film 110. Furthermore, since the film 110 has excellent sliding properties, when the film 110 is wound to form a film capacitor, the compressibility and self-healing properties are improved.

[0127] In a film capacitor, when measuring the average diameter, average height, and number of protrusions present on the first main surface of the film, the above method is used to measure the area where the metal layer is not provided on the metallized film located on the outermost surface of the film capacitor. At this time, if masking oil is attached to the surface of the measurement area, it is preferred to measure it in a state where the masking oil is removed using a solvent such as hexane or toluene.

[0128] In the film capacitor of the present invention, the metallized film of the present invention can be used as the metallized film.

[0129] The metallized film of the present invention comprises: a film including a first organic material having a hydroxyl group and a cured product of a second organic material having an isocyanate group among aromatic compounds, and having a first main surface and a second main surface facing each other in the thickness direction; and a metal layer provided on at least the first main surface of the film. In addition, in the metallized film of the present invention, a plurality of protrusions having the second organic material are present on the first main surface of the film. Furthermore, in the metallized film of the present invention, a plurality of convex portions along the plurality of protrusions are present on the surface of the metal layer provided on the first main surface of the film on the opposite side to the first main surface of the film.

[0130] In the first mode of the thin film capacitor of the present invention, similarly to the second mode of the thin film capacitor of the present invention described later, it is preferred that there are multiple protrusions along the multiple protrusions on the surface of the metal layer arranged on the first main surface of the dielectric film, which is opposite to the first main surface of the dielectric film.

[0131] In the first mode of the thin film capacitor of the present invention, when the above-mentioned multiple protrusions exist on the above-mentioned surface of the above-mentioned metal layer arranged on the above-mentioned first main surface of the above-mentioned dielectric film, similarly to the second mode of the thin film capacitor of the present invention described later, it is preferred that within the area range of 100μm×140μm of the above-mentioned surface of the above-mentioned metal layer, the average diameter of the above-mentioned multiple protrusions is greater than 0.60μm and less than 6.13μm, the average height is greater than 0.13μm and less than 2.63μm, and the number is greater than 50 and less than 450.

[0132] In a second aspect of the film capacitor of the present invention, a plurality of projections along the plurality of protrusions exist on a surface of the metal layer provided on the first main surface of the dielectric film opposite to the first main surface of the dielectric film.

[0133] exist Figure 7 as well as Figure 8 In the metallized film 210 shown, a plurality of convex portions 230 are present along a plurality of protrusions 120 on a surface 220a of the metal layer 220 opposite to the first main surface 110a of the film 110. In addition, a flat portion 240 is present on the surface 220a of the metal layer 220, where the convex portion 230 is not present.

[0134] The presence of the protrusions can be confirmed as black-looking portions by observing the surface of the metal layer with a scanning electron microscope.

[0135] In the metallized film of the present invention, within an area of ​​100 μm×140 μm on the surface of the metal layer, the average diameter of the plurality of protrusions is greater than 0.60 μm and less than 6.13 μm, the average height is greater than 0.13 μm and less than 2.63 μm, and the number is greater than 50 and less than 450.

[0136] In the second aspect of the film capacitor of the present invention, within an area of ​​100 μm×140 μm on the surface of the metal layer, the average diameter of the plurality of projections is 0.60 μm to 6.13 μm, the average height is 0.13 μm to 2.63 μm, and the number is 50 to 450. In this way, in the second aspect of the film capacitor of the present invention, attention is paid to the plurality of projections present on the surface of the metal layer.

[0137] exist Figure 7 as well as Figure 8In the metallized film 210 shown, within an area of ​​100 μm×140 μm on the surface 220 a of the metal layer 220 , the average diameter of the plurality of protrusions 230 is greater than 0.60 μm and less than 6.13 μm, the average height is greater than 0.13 μm and less than 2.63 μm, and the number is greater than 50 and less than 450.

[0138] The metallized film 210 has excellent sliding properties and withstand voltage properties because the average diameter of the plurality of protrusions 230 is 0.60 μm to 6.13 μm, the average height is 0.13 μm to 2.63 μm, and the number is 50 to 450 within the above-mentioned area range of the surface 220a of the metal layer 220. Furthermore, since the metallized film 210 has excellent sliding properties, when the metallized film 210 is wound to form a film capacitor, the compressibility and self-healing properties are improved.

[0139] When the average diameter of protrusions 230 is less than 0.60 μm, when metallized films 210 are slid together, the contact area between flat portions 240 is likely to increase, thereby reducing the slidability. When the average diameter of protrusions 230 is greater than 6.13 μm, when metallized films 210 are slid together, the contact area between protrusions 230 is likely to increase, thereby reducing the slidability.

[0140] When the average height of the protrusions 230 is less than 0.13 μm, the contact area between the flat portions 240 is likely to increase when the metallized films 210 slide against each other, thereby reducing the slidability. When the average height of the protrusions 230 is greater than 2.63 μm, the electric field is likely to concentrate near the protrusions 230, thereby reducing the withstand voltage.

[0141] When the number of protrusions 230 is less than 50, when the metallized films 210 are slid together, the contact area between the flat portions 240 is likely to increase, thereby reducing the slidability. When the number of protrusions 230 is more than 450, the number of locations where the electric field is likely to concentrate, such as the protrusions 230, increases, thereby reducing the withstand voltage.

[0142] Within the above-mentioned area range of the surface 220a of the metal layer 220, as long as the average diameter of the plurality of protrusions 230 is greater than 0.60 μm and less than 6.13 μm, the average height is greater than 0.13 μm and less than 2.63 μm, and the number is greater than 50 and less than 450, then in addition to the plurality of protrusions 230, a plurality of recesses may also exist on the surface 220a of the metal layer 220.

[0143] The average diameter of the protrusions present on the surface of the metal layer can be determined in the same manner as the average diameter of the protrusions present on the first main surface of the film, except that the observation object is the surface of the metal layer. More specifically, under the same setting conditions as when determining the average diameter of the protrusions present on the first main surface of the film, the following measurement is performed for each of the 30 protrusions: Figure 8 The width R2 of the convex portion 230 shown is determined by averaging the obtained measured values ​​as the average diameter of the convex portion.

[0144] The average height of the convex portions existing on the surface of the metal layer can be determined in the same manner as the average height of the protrusions existing on the first main surface of the film, except that the observation object is the surface of the metal layer. More specifically, under the same setting conditions as when determining the average height of the protrusions existing on the first main surface of the film, the following measurement is performed for each of the 30 convex portions: Figure 8 The height H2 of the convex portion 230 shown is determined by taking the average value of the obtained measured values ​​as the average height of the convex portion.

[0145] The number of convex portions existing on the surface of the metal layer can be determined in the same manner as the number of protrusions existing on the first main surface of the thin film, except that the observation target is the surface of the metal layer.

[0146] In a film capacitor, when measuring the average diameter, average height, and number of projections present on the surface of the metal layer, the measurement is performed at a predetermined region of the metallized film located on the outermost surface of the film capacitor.

[0147] exist Figure 3 In the wound body 40 shown, preferably, in the region L of the second metalized film 12 located on the outermost surface, in the state where the second metal layer 16 is provided, the average diameter, average height, and number of the protrusions existing on the surface of the second metal layer 16 are measured by the above-mentioned method. Here, the region L of the second metalized film 12 is a square shape whose length in the width direction W and the length direction (winding direction) are both M. In addition, when a center line Q passing through the center point P of the end side N of the second metalized film 12 and extending in the length direction is defined, the region L of the second metalized film 12 is line symmetric with respect to the center line Q in the width direction W. The length M of the region L of the second metalized film 12 is 10% of the length of the end side N of the second metalized film 12.

[0148] In the metallized film of the present invention, the static friction coefficient of the metal layer provided on the first main surface of the film on the surface side is preferably 1.4 or less.

[0149] In the first mode of the thin film capacitor of the present invention, when the above-mentioned multiple protrusions exist on the above-mentioned surface of the above-mentioned metal layer arranged on the above-mentioned first main surface of the above-mentioned dielectric film, the static friction coefficient of the above-mentioned metal layer arranged on the above-mentioned first main surface of the above-mentioned dielectric film on the above-mentioned surface side is preferably less than 1.4.

[0150] In a second aspect of the film capacitor of the present invention, it is preferred that the metal layer provided on the first main surface of the dielectric film has a static friction coefficient of 1.4 or less on the surface side.

[0151] exist Figure 7 as well as Figure 8 In the metalized film 210 shown, the static friction coefficient of the metal layer 220 on the surface 220a side is preferably 1.4 or less. In this case, the sliding property of the metalized film 210 becomes very excellent.

[0152] On the other hand, if the static friction coefficient of the metal layer 220 on the surface 220a side of the metalized film 210 becomes too small, the winding of the metalized film 210 may deviate in the width direction when the metalized film 210 is wound to manufacture a film capacitor, and it may be difficult to form an external electrode on the end surface of the obtained wound body in the subsequent process. From this point of view, the static friction coefficient of the metal layer 220 on the surface 220a side of the metalized film 210 is preferably 0.2 or more.

[0153] The static friction coefficient of the metallized film can be determined in the same manner as the static friction coefficient of the film, except that the metallized film is used as the measurement sample.

[0154] Examples of the constituent material of the metal layer 220 include metals such as aluminum, zinc, titanium, magnesium, tin, and nickel.

[0155] The thickness of the metal layer 220 is preferably greater than or equal to 5 nm and less than or equal to 40 nm.

[0156] The thickness of the metal layer can be determined by observing a cross section of the metallized film in the thickness direction using a transmission electron microscope (TEM).

[0157] The film of the present invention can be produced, for example, by the following method.

[0158] <Resin Solution Preparation Process>

[0159] The resin solution is prepared by mixing a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds.

[0160] As the first organic material and the second organic material, the above-mentioned materials can be used.

[0161] When preparing the resin solution, the first organic material and the second organic material may be diluted with a solvent. In particular, it is preferred that the first organic material and the second organic material be diluted with a mixed solvent containing a first solvent selected from ketones and a second solvent selected from cyclic ether compounds.

[0162] Examples of the ketone selected as the first solvent include methyl ethyl ketone and diethyl ketone.

[0163] As the first solvent, a plurality of ketones may be used in combination.

[0164] Examples of the cyclic ether compound selected as the second solvent include tetrahydrofuran and tetrahydropyran.

[0165] As the second solvent, a plurality of cyclic ether compounds may be used in combination.

[0166] As the solvent, a mixed solvent containing methyl ethyl ketone and tetrahydrofuran is preferably used.

[0167] <Resin Solution Drying / Curing Step>

[0168] First, a resin solution is applied to the surface of a substrate.

[0169] Examples of the substrate include polyethylene terephthalate films and polypropylene films.

[0170] Next, the obtained coating of the resin solution is dried in a drying furnace and then cured by heat treatment, thereby forming a thin film on the surface of the substrate.

[0171] At this time, the drying temperature, drying time, air volume, etc. in the drying furnace are adjusted for the coating of the resin solution, so that the second organic material, i.e., aromatic isocyanate, is condensed on the dry surface of the coating, which is the main surface opposite to the substrate, and a plurality of protrusions are generated as the condensed product, and further, the specifications of the protrusions are controlled. As a result, in the state of a thin film obtained by curing the coating, within the area of ​​100 μm×140 μm of the first main surface corresponding to the dry surface, the specifications of the plurality of protrusions can be controlled to be an average diameter of 0.58 μm or more and 5.98 μm or less, an average height of 0.11 μm or more and 2.54 μm or less, and a number of 50 or more and 450 or less.

[0172] The drying temperature of the coating film is preferably adjusted within a range of 70° C. to 150° C.

[0173] The drying time of the coating film can be adjusted by the conveying speed of the substrate with the coating film in the drying furnace. The conveying speed is preferably adjusted within the range of 100 m / min to 160 m / min.

[0174] In addition, the film obtained is used under the state of peeling off from base material. As mentioned above, the 1st principal surface of the film is equivalent to the dry surface as the principal surface on the opposite side of the base material in the coating film. In addition, the 2nd principal surface of the film is equivalent to the demoulding surface as the principal surface on the base material side in the coating film.

[0175] Based on the above, make Figure 5 as well as Figure 6 film shown.

[0176] The metallized film of the present invention can be produced, for example, by the following method.

[0177] <Metalized Film Production Process>

[0178] First, by the above-mentioned thin film manufacturing method of the present invention, as the first dielectric thin film and the second dielectric thin film, the following are manufactured: Figure 5 as well as Figure 6 film shown.

[0179] Next, a first metal layer is formed by evaporating a metal on the first main surface of the first dielectric film, thereby manufacturing a first metalized film. At this time, the first metal layer is formed so that a plurality of convex portions along the plurality of protrusions of the first dielectric film exist on the surface of the first metal layer on the opposite side to the first main surface of the first dielectric film. Furthermore, the first metal layer is formed so that it reaches one side edge of the first dielectric film in the width direction and does not reach the other side edge of the first dielectric film.

[0180] In addition, a second metal layer is formed by evaporating a metal on the first main surface of the second dielectric film, thereby manufacturing a second metalized film. At this time, the second metal layer is formed so that a plurality of convex portions along the plurality of protrusions of the second dielectric film exist on the surface of the second metal layer on the opposite side to the first main surface of the second dielectric film. Furthermore, the second metal layer is formed so that it does not reach one side edge of the second dielectric film in the width direction but reaches the other side edge of the second dielectric film.

[0181] Through this process, as the first metallized film and the second metallized film, Figure 7 as well as Figure 8 The metallized film shown.

[0182] The film capacitor of the present invention can be produced, for example, by the following method.

[0183] <Wound body production process>

[0184] First, by the above-mentioned method for manufacturing a metallized film of the present invention, a first metallized film and a second metallized film are prepared as follows: Figure 7 as well as Figure 8The metallized film shown.

[0185] Next, the first metallized film and the second metallized film are stacked and wound up in a state where they are offset by a given distance in the width direction, thereby producing a wound body. In addition, the wound body can be pressed into an elliptical cylindrical shape by clamping it in a direction perpendicular to the width direction as required.

[0186] <External Electrode Formation Step>

[0187] A first external electrode is formed by thermally spraying a metal on one end surface of the wound body so as to be connected to the first metal layer.

[0188] Furthermore, a second external electrode is formed by thermally spraying a metal on the other end surface of the wound body so as to be connected to the second metal layer.

[0189] According to the above, manufacture Figure 1 as well as Figure 2 The film capacitor shown.

[0190] The film capacitor of the present invention can be applied to known uses, but since it can extend the life of equipment used in a high-temperature environment with large temperature changes, it is suitable for use in power electronic equipment such as electric compressors / pumps, chargers, DC-DC converters, and drive inverters installed in automobiles, industrial equipment, etc.

[0191] [Example]

[0192] Hereinafter, examples are shown which more specifically disclose the film capacitor of the present invention, the film of the present invention, and the metallized film of the present invention. However, the present invention is not limited to these examples.

[0193] Thin film samples 1 to 9 were produced by the following method.

[0194] <Resin Solution Preparation Process>

[0195] A phenoxy resin and MDI were diluted with a mixed solvent of methyl ethyl ketone and tetrahydrofuran and mixed to prepare a resin solution.

[0196] <Resin Solution Drying / Curing Step>

[0197] First, the resin solution was applied to the surface of a polyethylene terephthalate film using a gravure coater.

[0198] Next, the obtained coating of the resin solution was dried in a drying oven and then cured by heat treatment for a certain period of time. Thus, film samples 1 to 9 each having a thickness of 4.5 μm were prepared on the surface of the polyethylene terephthalate film.

[0199] At this time, for the coating of the resin solution, the drying temperature is adjusted within the range of not less than 70°C and not more than 150°C, and further, the conveying speed in the drying furnace is adjusted within the range of not less than 100 m / min and not more than 160 m / min, so that the generation conditions of the protrusions having MDI on the first main surface of the film samples 1 to 9 are different, and further, the specifications of the protrusions are different.

[0200] Then, the obtained film samples 1 to 9 were peeled off from the polyethylene terephthalate film.

[0201] Furthermore, a film sample 10 was produced in the same manner as for the film samples 1 to 9 except that hexamethylene diisocyanate (HDI) was added as an aliphatic polyisocyanate instead of MDI to the resin solution used in producing the film samples 1 to 9.

[0202] In addition, a film sample 11 having no protrusions on the first main surface was manufactured using the same resin solution as that used in manufacturing film samples 1 to 9. Furthermore, a filler was further blended into the resin solution used in manufacturing film sample 11, and the blending ratio of the filler was changed, thereby manufacturing film samples 12 to 14. The blending ratio of the filler was 1% by weight in film sample 12, 3% by weight in film sample 13, and 10% by weight in film sample 14, relative to the total weight of the phenoxy resin and MDI. Acrylic beads "MP-1451" (average particle size: 0.15 μm) manufactured by Soken Chemical Co., Ltd. were used as fillers.

[0203] [evaluate]

[0204] For the film samples 1 to 9 having protrusions on the first main surface, it was confirmed by the above method that the protrusions had MDI. For film sample 10, it was confirmed that the protrusions had HDI. For film sample 11, it was confirmed that there were no protrusions on the first main surface. For film samples 12 to 14, it was confirmed that the first main surface was roughened due to the filler.

[0205] Furthermore, the following evaluations were performed on the film samples 1 to 14. The results are shown in Table 1. In Table 1, the film samples are simply described as "samples".

[0206] <Average diameter of protrusions>

[0207] Regarding film samples 1 to 10, the average diameter of the protrusions was measured by the above-mentioned method.

[0208] <Average height of protrusions>

[0209] Regarding film samples 1 to 10, the average height of the protrusions was measured by the above-mentioned method.

[0210] <Number of protrusions>

[0211] Regarding film samples 1 to 10, the number of protrusions was counted by the above-mentioned method.

[0212] <Average diameter of convex portion>

[0213] Metallized films were produced by forming a metal layer by vapor-depositing aluminum on the first main surfaces of film samples 1 to 10. Then, the average diameter of the projections of the obtained metallized films was measured by the above-mentioned method.

[0214] <Average height of convex parts>

[0215] Metallized films were produced by forming a metal layer by vapor-depositing aluminum on the first main surfaces of film samples 1 to 10. Then, the average height of the protrusions of the obtained metallized films was measured by the above-mentioned method.

[0216] <Number of convex parts>

[0217] Metallized films were produced by forming a metal layer by vapor-depositing aluminum on the first main surfaces of film samples 1 to 10. Then, the number of protrusions on the obtained metallized films was counted by the above-mentioned method.

[0218] <Glass transition temperature>

[0219] The glass transition temperatures of the film samples 1 to 10 were measured by the above-mentioned method.

[0220] <Static friction coefficient 1>

[0221] The static friction coefficient was measured by the above-mentioned method for the film samples 1 to 14. In Table 1, the static friction coefficient in the state of the film is described as "static friction coefficient 1".

[0222] <Static friction coefficient 2>

[0223] A metal layer was formed by vapor-depositing aluminum on the first main surface of the film samples 1 to 14, thereby producing a metalized film. Then, the static friction coefficient of the obtained metalized film was measured by the above-mentioned method. In addition, in Table 1, the static friction coefficient in the state of the metalized film is recorded as "static friction coefficient 2".

[0224] <Dielectric Breakdown Voltage>

[0225] First, aluminum was vapor-deposited on both main surfaces of the film samples 1 to 14 to form metal layers, thereby preparing the measurement samples. At this time, the area of ​​the region where the metal layers vapor-deposited on both main surfaces of the film samples overlapped each other was set to 3 cm 2. For each of the film samples 1 to 14, 16 such test samples were made. Secondly, for the 16 test samples, each electric field strength was maintained for 10 minutes at an electric field strength of 25V / μm, and the electric field strength when 8 breakdown marks were generated in the film sample was set as the failure voltage. Regarding the measurement temperature, it was set to 125°C. Then, the failure voltages of the 16 test samples were Weibull plotted, and the value at which the failure frequency in the Weibull distribution became 50% was adopted as the insulation breakdown voltage of the film sample.

[0226] <Repressive>

[0227] First, a metal layer was formed by vapor-depositing aluminum on the first main surface of film samples 1 to 14, thereby producing a metalized film. At this time, in order to give the metal layer a pattern, a fluorine-based oil was pre-coated on the first main surface of the film sample. Next, after the metalized film was cut into a given width, it was wound into a cylindrical shape to a given length to produce a wound body. Then, according to the size of the wound body, the wound body was pressed while appropriately adjusting the applied pressure within the range of more than 10N and less than 100N, and then an evaluation was performed to determine whether the wound body was evenly pressed. Regarding the evaluation index, when the wound body is observed in the width direction (refer to Figure 3 ), the case where the film along the inner side of the gap portion at the center of the winding has no wrinkles / breaks is marked as ○ (good), and the case where the film along the inner side of the gap portion at the center of the winding has wrinkles / breaks is marked as × (bad).

[0228] <Self-healing property>

[0229] First, a metal layer was formed by vapor-depositing aluminum on the first main surface of film samples 1 to 14, thereby producing a metalized film. At this time, in order to make the metal layer have a pattern, a fluorine-based oil was pre-coated on the first main surface of the film sample. Secondly, after the metalized film was cut into a given width, it was wound into a cylindrical shape with a given length to produce a wound body. Then, external electrodes were formed by spraying metal on both end surfaces of the obtained wound body, thereby producing a film capacitor. Then, while applying a voltage to the obtained film capacitor, the applied voltage was gradually increased, and it was evaluated whether the applied voltage was restored to the original applied voltage even if the applied voltage dropped instantly during insulation breakdown. Regarding the evaluation index, the case where the original applied voltage was restored was set to ○ (good), and the case where the original applied voltage was not restored was set to × (bad).

[0230] [Table 1]

[0231]

[0232] In Table 1, the sample names with an asterisk (*) are comparative examples outside the scope of the present invention.

[0233] According to the above, in film samples 1 to 4, it was confirmed that protrusions with an aromatic isocyanate and an average diameter of 0.58 μm to 5.98 μm, an average height of 0.11 μm to 2.54 μm, and a number of 50 to 450 were present on the first main surface. In addition, it was confirmed that in the state where the metal layer was evaporated on the first main surface of film samples 1 to 4 to make a metallized film, convex portions with an average diameter of 0.60 μm to 6.13 μm, an average height of 0.13 μm to 2.63 μm, and a number of 50 to 450 were present on the surface of the metal layer. According to such film samples 1 to 4, excellent sliding properties and voltage resistance can be obtained, and further, the compressibility and self-healing properties of the film capacitor can be made excellent. More specifically, according to the film samples 1 to 4, very excellent sliding properties due to low static friction coefficients 1 and 2, and very excellent voltage resistance such as a dielectric breakdown voltage of 300V / μm or more can be obtained, and further, the compressibility and self-healing properties of the film capacitor can be made excellent. In addition, in the film samples 1 to 4, the glass transition temperature is above 130°C, and the heat resistance is also excellent.

[0234] In film sample 5, the average diameter of the protrusions is less than 0.58 μm, and the number of protrusions is more than 450. In addition, in the state where the metal layer is evaporated on the first main surface of film sample 5 to make a metallized film, the average diameter of the protrusions is less than 0.60 μm, and the number of protrusions is more than 450. Therefore, according to film sample 5, compared with film samples 1 to 4, the static friction coefficient 1 and the static friction coefficient 2 are high, the insulation breakdown voltage becomes low, and the compressibility and self-healing properties of the film capacitor cannot be made excellent.

[0235] In film sample 6, the number of protrusions is 0, that is, there are no protrusions. In addition, in the state where the metal layer is evaporated on the first main surface of film sample 6 to make a metalized film, the number of convex parts is 0, that is, there are no convex parts. Therefore, according to film sample 6, compared with film samples 1 to 4, the static friction coefficient 1 and the static friction coefficient 2 become higher, and the compressibility and self-healing properties of the film capacitor cannot be improved.

[0236] In film sample 7, the average height of the protrusions was greater than 2.54 μm. In addition, in a state where a metal layer was deposited on the first main surface of film sample 7 to form a metallized film, the average height of the protrusions was greater than 2.63 μm. Therefore, according to film sample 7, the dielectric breakdown voltage is lower than that of film samples 1 to 4.

[0237] In film sample 8, the average height of the protrusions was less than 0.11 μm. In addition, in a state where a metal layer was deposited on the first main surface of film sample 8 to form a metallized film, the average height of the protrusions was less than 0.13 μm. Therefore, according to film sample 8, compared with film samples 1 to 4, the static friction coefficient 1 and the static friction coefficient 2 became higher, and the compressibility and self-healing properties of the film capacitor could not be improved.

[0238] In film sample 9, the average diameter of the protrusions was greater than 5.98 μm. In addition, in a state where a metal layer was deposited on the first main surface of film sample 9 to form a metallized film, the average diameter of the protrusions was greater than 6.13 μm. Therefore, according to film sample 9, compared with film samples 1 to 4, the static friction coefficient 1 and the static friction coefficient 2 became higher, and the compressibility and self-healing properties of the film capacitor could not be improved.

[0239] In the film sample 10, since the protrusions contained aliphatic isocyanate, the self-healing property of the film capacitor could not be improved.

[0240] In film sample 11, there are no protrusions. In addition, in the state where the metal layer is deposited on the first main surface of film sample 11 to form a metalized film, there are no convex parts. Therefore, according to film sample 11, compared with film samples 1 to 4, the static friction coefficient 1 and the static friction coefficient 2 become higher, and the compressibility and self-healing properties of the film capacitor cannot be improved.

[0241] Film samples 12 to 14 contain fillers, so the dielectric breakdown voltage is lower than that of film samples 1 to 4. In addition, according to film sample 12, the static friction coefficient 1 and the static friction coefficient 2 are higher than those of film samples 1 to 4, and the compressibility and self-healing properties of the film capacitor cannot be improved.

[0242] Description of Reference Numerals

[0243] 10. Film capacitors;

[0244] 11 No. 1 metallized film;

[0245] 12 No. 2 metallized film;

[0246] 13. 1st dielectric film;

[0247] 13a a first main surface of a first dielectric film;

[0248] 13b a second main surface of the first dielectric film;

[0249] 14. 2nd dielectric film;

[0250] 14a: a first main surface of a second dielectric film;

[0251] 14b a second main surface of the second dielectric film;

[0252] 15 1st metal layer;

[0253] 16 2nd metal layer;

[0254] 40 winding body;

[0255] 41 1st external electrode;

[0256] 42 2nd external electrode;

[0257] 61: split electrode portion;

[0258] 62 electrode part;

[0259] 63 fuse unit;

[0260] 64 insulation slits;

[0261] 110 thin film (dielectric film);

[0262] 110a: a first main surface of the film;

[0263] 110b: the second main surface of the film;

[0264] 120 film protrusions;

[0265] 130 a flat portion of the film;

[0266] 210 metallized film;

[0267] 220 metal layer;

[0268] 220a: a surface of a metal layer;

[0269] 230 a convex portion of the metal layer;

[0270] 240 a flat portion of the metal layer;

[0271] Height of H1 protrusion;

[0272] H2 height of the convex part;

[0273] L is the area of ​​the second metallized film;

[0274] M is the length of the region of the second metallized film;

[0275] N the end edge of the second metallized film;

[0276] P is the center point of the end edge of the second metallized film;

[0277] Q center line;

[0278] Width of R1 protrusion;

[0279] R2 width of the convex part;

[0280] S film thickness;

[0281] T stacking direction;

[0282] W width direction.

Claims

1. A film capacitor, characterized in that: A wound body is provided in which a dielectric film and a metal layer are wound, wherein the dielectric film includes a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and has a first main surface and a second main surface facing each other in a thickness direction, and the metal layer is provided on at least the first main surface of the dielectric film. On the first main surface of the dielectric film, there are a plurality of protrusions having the second organic material. Within an area of ​​100 μm×140 μm on the first main surface of the dielectric film, the plurality of protrusions have an average diameter of 0.58 μm to 5.98 μm, an average height of 0.11 μm to 2.54 μm, and a number of 50 to 450.

2. The film capacitor according to claim 1, characterized in that: A plurality of convex portions along the plurality of protrusions exist on a surface of the metal layer provided on the first main surface of the dielectric film, which is opposite to the first main surface of the dielectric film.

3. The film capacitor according to claim 2, characterized in that: The metal layer provided on the first main surface of the dielectric film has a static friction coefficient of 1.4 or less on the surface side.

4. The film capacitor according to any one of claims 1 to 3, characterized in that: When the cross section of the wound body is observed perpendicular to the winding axis direction, the cross-sectional shape of the wound body is a flat shape.

5. A film capacitor, characterized in that: A wound body is provided in which a dielectric film and a metal layer are wound, wherein the dielectric film includes a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and has a first main surface and a second main surface facing each other in a thickness direction, and the metal layer is provided on at least the first main surface of the dielectric film. On the first main surface of the dielectric film, there are a plurality of protrusions having the second organic material. A plurality of convex portions along the plurality of protrusions are present on a surface of the metal layer provided on the first main surface of the dielectric film, which surface is opposite to the first main surface of the dielectric film. Within an area of ​​100 μm×140 μm on the surface of the metal layer, the plurality of projections have an average diameter of 0.60 μm to 6.13 μm, an average height of 0.13 μm to 2.63 μm, and a number of 50 to 450.

6. The film capacitor according to claim 5, characterized in that: The metal layer provided on the first main surface of the dielectric film has a static friction coefficient of 1.4 or less on the surface side.

7. The film capacitor according to claim 5 or 6, characterized in that: When the cross section of the wound body is observed perpendicular to the winding axis direction, the cross-sectional shape of the wound body is a flat shape.

8. A film, characterized in that: A cured product comprising a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and having a first main surface and a second main surface facing each other in the thickness direction, On the first main surface, there are a plurality of protrusions having the second organic material. Within an area of ​​100 μm×140 μm on the first main surface, the plurality of protrusions have an average diameter of 0.58 μm to 5.98 μm, an average height of 0.11 μm to 2.54 μm, and a number of 50 to 450.

9. The film according to claim 8, characterized in that The static friction coefficient on the first main surface side is 1.0 or less.

10. A metallized film, characterized in that: have: A thin film comprising a cured product of a first organic material having a hydroxyl group and a second organic material having an isocyanate group among aromatic compounds, and having a first main surface and a second main surface facing each other in a thickness direction; and a metal layer disposed on at least the first main surface of the film, On the first main surface of the film, there are a plurality of protrusions having the second organic material. A plurality of convex portions along the plurality of protrusions are present on a surface of the metal layer provided on the first main surface of the film on the opposite side to the first main surface of the film, Within an area of ​​100 μm×140 μm on the surface of the metal layer, the plurality of projections have an average diameter of 0.60 μm to 6.13 μm, an average height of 0.13 μm to 2.63 μm, and a number of 50 to 450.

11. The metallized film according to claim 10, characterized in that: The metal layer provided on the first main surface of the film has a static friction coefficient of 1.4 or less on the surface side.

Citation Information

Patent Citations

  • Film capacitor and metallized film thereof

    JP1993251266A

  • Metalized film capacitor

    JP2004363431A

  • Cover tape for packaging electronic component

    JP2011251493A

  • Film capacitor, connected-type capacitor, inverter, and electric vehicle

    CN109478462A

  • Micro Mold for Manufacturing a Micro Pattern Film for Security Film and Method of Manufacturing the Micro Mold

    KR101303118B1